2022
DOI: 10.1093/cid/ciac402
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine and Mupirocin for Clearance of Methicillin-Resistant Staphylococcus aureus Colonization After Hospital Discharge: A Secondary Analysis of the Changing Lives by Eradicating Antibiotic Resistance Trial

Abstract: BACKGROUND The CLEAR trial demonstrated that a multi-site body decolonization regimen reduced post-discharge infection and hospitalization in methicillin-resistant Staphylococcus aureus (MRSA) carriers. This report describes decolonization efficacy in clearing site-specific MRSA colonization during the trial. METHODS We performed a large, multi-center, randomized clinical trial of MRSA decolonization among adult patients afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Swabs were obtained from multiple body sites including nares, throat, skin (axilla and groin), as well as accessible wounds, if present. While the trial demonstrated the benefit of the decolonization protocol with chlorhexidine and mupirocin, persistent colonization was noted in a subset of both trial arms [ 15 ]. The factors that contributed to persistent colonization were not addressed in the primary manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Swabs were obtained from multiple body sites including nares, throat, skin (axilla and groin), as well as accessible wounds, if present. While the trial demonstrated the benefit of the decolonization protocol with chlorhexidine and mupirocin, persistent colonization was noted in a subset of both trial arms [ 15 ]. The factors that contributed to persistent colonization were not addressed in the primary manuscript.…”
Section: Introductionmentioning
confidence: 99%